Religious Social Program: Tahsin Qira'ah for Parents and Children in Medan Marelan - Muhammad Sapii Harahap; Sopian Sinaga; Dwi Wulandari; Lailatul Maghfirah; Shalini; Syafiqa Ashikin; Ummul Husna; Yamila Azzahrah (ASSUNNAH PRESS, 2023)
Many parents do not care about learning the Al-Qur'an for their children. Most parents are more concerned with general subjects such as tutoring English, mathematics, and physics. Meanwhile, learning the Al-Qur'an is neglected. This research aims to assist parents and children in learning the Al-Qur'an in Neighborhood 09, Rengas Pulau Village, Medan Marelan District. This community service activity uses the PAR (Participatory Action Research) method. With this method, community service participants try to assist the community to solve existing problems. Community contribution is needed in this activity because it is hoped that after this activity, the community can stand independently in religious empowerment and overcome issues. To assist the community in dealing with existing problems activities to strengthen Al-Qur'an reading and writing were held for parents and children. This community service research results show positive changes in parents and children alike. Among them is their awareness of the importance of studying the Al- Qur'an, filling their time with useful things, and the community's enthusiasm for good things. Overall the KKN activities carried out by STAI As-Sunnah students went well. With the existence of this KKN activity, it can reduce the problems that exist in the midst of the community